Concentrating solar power: a renewable energy frontier. Issue 3 (4th May 2014) - Mathews, John A.; Hu, Mei-Chih; Wu, Ching-Yan
Abstract : Renewable energies are advancing across many fronts – and now a new front has opened up in the form of dispatchable concentrating solar power (CSP). It is in emerging markets such as China, India and countries in North Africa and the Middle East as well as South America and southern Africa that CSP power plants with 24/7 dispatchable power are starting to be viewed as a viable way forward. The emerging CSP industrial value chain in China, India, southern Africa and elsewhere is expected to exert its consequent dramatic impact on cost reductions, which will in turn drive the diffusion of CSP around the world as a key challenger and alternative to nuclear and fossil fuel power. In this paper, we review these developments and discuss the effects attributable to the emerging learning curve, combined with technology progress involving molten salt heat transfer and reductions in water requirements, as well as patenting trends in the global CSP industry.